\(\left(x-3\right)^2+\frac{1}{2}=\left(x-1\right)\cdot\left(x+1\right)\)
\(x^2-6x+9+\frac{1}{2}=x^2-1\)
\(x^2-6x+9\frac{1}{2}=x^2-1\)
\(x^2-6x-x^2=-1-9\frac{1}{2}\)
\(\left(x^2-x^2\right)-6x=-10\frac{1}{2}\)
\(-6x=-10\frac{1}{2}\)
\(x=-10\frac{1}{2}:\left(-6\right)\)
\(x=1\frac{3}{4}\)
(x-3)^2 +1/2= (x-1)*(x+1)
\(\Leftrightarrow x^2-6x+\frac{19}{2}=x^2-1\)
\(\Leftrightarrow x^2-6x+\frac{19}{2}-x^2+1=0\)
\(\Leftrightarrow\left(x^2-x^2\right)+\frac{19}{2}+1-6x=0\)
\(\Leftrightarrow\frac{21}{2}-6x=0\)
\(\Leftrightarrow\frac{21}{2}-\frac{12x}{2}=0\)
\(\Leftrightarrow-\frac{3\left(4x-7\right)}{2}=0\)
\(\Leftrightarrow3\left(4x-7\right)=0\)
\(\Leftrightarrow4x-7=0\)
\(\Leftrightarrow4x=7\)
\(\Leftrightarrow x=\frac{7}{4}\)
x^2 - 6x + 19/12 = x^2 - 1
21/2 - 6x = 0
-3 ( 4x -7) / 2=0
4 x = 7
(-6)^2 - ( 4 * 0 * 21/2 )=36
suy ra sẽ được 7/4